2022
DOI: 10.1037/ort0000591
|View full text |Cite
|
Sign up to set email alerts
|

Parental perceived immigration threat and children’s mental health, self-regulation and executive functioning in pre-Kindergarten.

Abstract: Many children in immigrant households endure unique stressors shaped by national, state, and local immigration policies and enforcement activity in the United States. Qualitative studies find that during times of heightened immigration enforcement, children as young as 3 years of age show signs of behavioral distress related to national anti-immigrant sentiment and the possibility of losing a parent. Using multiple sources of data from 168 racially and ethnically diverse families of children in pre-Kindergarte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…The rise in negative sentiments towards Latinx immigrants has led to the depiction that they are a threat to national security and to the characterization of them as criminals involved in violent crimes and trafficking illegal narcotics. 56 , 57 This is especially true of immigrants from Mexico who were often the target of the 45 th President's anti-Latinx rhetoric in which he accused “Mexico of sending criminals, rapists, and drug dealers to the United States.” 58 To date, most of the research on the internalization of anti-immigrant and anti-Latinx rhetoric and psychological stress has been conducted with children, adolescents, and high school students (see 40 , 59 61 ). However, recent research is now highlighting how the current anti-immigrant climate that subjects Latinx immigrant adults to discrimination, deportation, and anti-immigrant rhetoric has contributed to members of the community internalizing these negatively charged messages and labeling them as stressful life events.…”
Section: Immigrant Rhetoricmentioning
confidence: 99%
“…The rise in negative sentiments towards Latinx immigrants has led to the depiction that they are a threat to national security and to the characterization of them as criminals involved in violent crimes and trafficking illegal narcotics. 56 , 57 This is especially true of immigrants from Mexico who were often the target of the 45 th President's anti-Latinx rhetoric in which he accused “Mexico of sending criminals, rapists, and drug dealers to the United States.” 58 To date, most of the research on the internalization of anti-immigrant and anti-Latinx rhetoric and psychological stress has been conducted with children, adolescents, and high school students (see 40 , 59 61 ). However, recent research is now highlighting how the current anti-immigrant climate that subjects Latinx immigrant adults to discrimination, deportation, and anti-immigrant rhetoric has contributed to members of the community internalizing these negatively charged messages and labeling them as stressful life events.…”
Section: Immigrant Rhetoricmentioning
confidence: 99%
“…For example, in a sample of 1040 youth, despite all living in low-income neighborhoods, adolescents with foreign-born parents had higher levels of internalizing behaviors compared to those with native-born parents (Lara-Cinisomo, Xue, & Brooks-Gunn, 2013). Heightened susceptibility may be due to immigrant parents' cultural preferences for informal care (Brandon, 2004;Fuller-Thomson & Minkler, 2007), the experience of cultural barriers when attempting to access formal care (Buriel & Hurtado-Ortiz, 2000), misunderstandings regarding the government-sponsored programs children qualify for due to precarious parental legal status (Suarez-Orozco & Suarez-Orozco, 2015), and perceived immigration threat (Barajas-Gonzalez et al, 2022;Ursache et al, 2022). Parental perceived immigration threat in the neighborhood for example, has been linked to lower selfregulation and greater overanxious behaviors among preschoolaged children of immigrants (Barajas-Gonzalez et al, 2022).…”
Section: Young Children Of Immigrants In the United Statesmentioning
confidence: 99%
“…Heightened susceptibility may be due to immigrant parents' cultural preferences for informal care (Brandon, 2004;Fuller-Thomson & Minkler, 2007), the experience of cultural barriers when attempting to access formal care (Buriel & Hurtado-Ortiz, 2000), misunderstandings regarding the government-sponsored programs children qualify for due to precarious parental legal status (Suarez-Orozco & Suarez-Orozco, 2015), and perceived immigration threat (Barajas-Gonzalez et al, 2022;Ursache et al, 2022). Parental perceived immigration threat in the neighborhood for example, has been linked to lower selfregulation and greater overanxious behaviors among preschoolaged children of immigrants (Barajas-Gonzalez et al, 2022). More specifically, the higher the perceived threat of immigration enforcement, the more fear and separation anxiety these young children demonstrated.…”
Section: Young Children Of Immigrants In the United Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…This constant threat of familial separation and chronic uncertainty is theorized to have direct impacts on children both through deprivation and threat pathways ( Barajas-Gonzalez et al, 2018 , 2021 ). Although no studies have yet investigated direct impacts of immigration raids or ICE presence on child self-regulation, recent work has shown that immigration enforcement threat more generally is related to self-regulation in children in Pre-K (according to parent report), although it was unexpectedly related to higher ratings of self-regulation by independent observers ( Barajas-Gonzalez et al, 2022b ). This work suggests that neighborhood level factors such as ICE presence and raids—which likely increase immigration enforcement threat for children and families—may have impacts on children’s self-regulation skills.…”
Section: Linking Neighborhood Social and Built Environments To Childr...mentioning
confidence: 99%